Mental health needs of people who identify as transgender: A review of the literature - Mc Cann, Edward; Sharek, Danika (My University, 2016)
Transgender people face many challenges in society including accessing and using healthcare systems. However, little is known about the specific mental health service needs and concerns of transgender people in this regard. The aim of the study was to establish the mental health service needs of transgender people through a review of relevant studies that address the experiences and views of this group. A comprehensive search of CINHAL, Cochrane, Google Scholar, PubMed, PsychInfo, PsychLit, Sociological Abstracts, Scopus, and Web of Science databases from inception to January 2014 was conducted. Studies were identified that met specific criteria that included: using qualitative methods, involving transgender people, and addressing issues related to mental health services. The search yielded 217 papers in total. Following the application of rigorous inclusion and exclu- sion criteria 33 papers were included for retrieval. Finally, 10 papers were considered suitable for the review. The data were analyzed and key themes identified. The review highlighted distinct challenges that exist in terms of mental health service provision. These included accessing appropriate services and treatments, responsiveness of practitioner’s, the provision of family supports and potential mental health service developments. The review findings are discussed and key recommendations are made in terms of mental health nursing practice developments, education and research.
PUBLISHED
Keywords: Sexuality; Transgender; LGBT; Mental health; Social inclusion; Inclusive Society; Health attitudes and behaviour; Health status and inequalities; Mental health nursing; Mental health promotion; Research issues specifice to any health profession; Sociological influences on health